Novel Validated RP-HPLC Method for Simultaneous Estimation of Valsartan & Gliclazide in Bulk and Dosage Forms - Patra, Rasmita; Reddy, Prakash N.; Kumar, N.S. Sampath; Dirisala, Vijaya R. (Current Pharmaceutical Analysis, 2018)
Objective: To devise a rapid, simple, selective and sensitive High Performance Liquid Chromatography (HPLC) method for simultaneous estimation of hypertension drug Valsartan and diabetic drug Gliclazide in bulk and dosage forms. Methods: Valsartan and Gliclazide were measured using the HPLC method with UV detector at 234 nm wave length. Drug analytes were separated on 5μm inertsil C18 column (4.6x250mmx5μm) using 55:45 v/v 10mM phosphate buffer pH 4.8, acetonitrile and 100μl of triethanolamine as mobile phase at a flow rate of 1 ml/min. Results: Chromatograms of high resolution were obtained and the retention times of Valsartan and Gliclazide were 2.50 and 3.71 minutes respectively. The method was linear over the concentrations ranging from 2-20μg/ml for Valsartan and 3-15μg/ml for Gliclazide respectively. The percentage assays of Valsartan and Gliclazide in active pharmaceutical ingredient were found to be 99.27 % and 98.55 % respectively. The devised method was validated by determining its accuracy, precision and system suitability. Conclusion: The results showed good reproducibility and are within the acceptable limits. It was demonstrated that the method can be successfully applied for the routine determination of Valsartan and Gliclazide in bulk and in its pharmaceutical dosage forms.
Keywords: active pharmaceutical ingredient